Abstinence Analysis in Air Molek 1 Village, Pasir Turtle District, Indragiri Hulu Regency - Liana Mulkufya; Supriyadi; Rian Hidayat (UIR Press, 2022)
Abstinence is a tradition that describes a socio-cultural life of the community that has a certain meaning that parents want to convey in educating their children. The problem in this research is how are the social values contained in abstinence in Air Molek 1 Village, Pasir Turtle District, Indragiri Hulu Regency? The purpose of this study is to describe, analyze, interpret, and conclude the social values found in Air Molek 1 Village, Pasir Turtle District, Indragiri Hulu Regency. The method used is descriptive. The data source is the expression of abstinence that was conveyed to the community in Air Molek 1 Village, Pasir Turtle District, Indragiri Hulu Regency. The approach in this research is qualitative. The type of research is field research. The results of this study indicate that abstinence contains social values found in Air Molek 1 Village, Pasir Turtle District, Indragiri Hulu Regency, namely material values, vital values, and spiritual values. For material values, there are 4 data for abstinence, for vital values there are 5 data for abstinence, for spiritual values there are 34 data for abstinence.